Nature and meaning of occupation for young men with tetraplegia living on the Cape Flats - Beeton, Hilary Jane (Division of Occupational Therapy, 2017)
In this qualitative study, in-depth interviews with three young men with tetraplegia, who have resumed living in their pre-injury environments on the Cape Flats, were used to uncover the meanings they attach to their everyday occupations. The aim of the study was to gain a deeper understanding of the nature and meaning of their occupations. Themes which emerged from an inductive analysis of the data: "It's a boring life", "Feeling trapped" and "Struggling to find a way", indicated that the most prevalent experience of occupation, was its limited and monotonous repertoire. Contextual barriers served to restrict opportunities for meaningful occupation. However, tentative meaning making through occupational strategies was evident. Occupations supporting meaningful relationships were highly valued in the absence of physical capacity. The contribution of occupation to re-defining self identity following a major life disruption, was discovered in relation to the themes. The findings have implications for clinical practice aimed at enabling occupation and for policy development.